Meaning in life as a mediator of dark triad with confidence in treatment and subjective evaluation of treatment outcome among male drug abstainers - Shi, Liping; Sun, Shijin; Zhu, Xueli; Geng, Yaoguo (Frontiers in Psychiatry, 2022)
Background: Although the roles of personality in predicting substance abuse has been widely documented, few studies have investigated the relations the Dark Triad (DT) personalities had with confidence in treatment (CIT) and subjective evaluation of treatment outcome (SETO) in drug abstainers. Objective: This study examined the relationship of DT and treatment relevant variables, and the potential effect of MIL in these links. Methods: Participants were male inpatients who started substance abuse treatment between June and December 2018 in Henan Province, China. Inclusion criteria were the diagnosis of substance use disorders. Exclusion criteria were illiteracy, comorbidity with psychopathology disorders, mental retardation, and refusal of consent. A total of 236 males (aged 21-62 years, M = 45.30, SD = 7.72) were randomly selected and reported their DT, MIL, CIT and SETO. Results: Results showed that DT was negatively correlated with MIL, CIT and SETO. MIL was positively correlated with CIT and SETO. Dark triad associated with CIT both directly and indirectly via MIL. DT indirectly correlated with SETO via MIL. Higher level of DT in drug abstainers can reduce CIT and SETO by decreasing individual’s MIL. Conclusion: This study provides insights into the links between Dark Triad and treatment relevant variables, which can potentially impact the effectiveness of current substance abuse treatment programs.